2014
DOI: 10.2337/db14-0595
|View full text |Cite
|
Sign up to set email alerts
|

Circulating FGF21 Is Liver Derived and Enhances Glucose Uptake During Refeeding and Overfeeding

Abstract: Fibroblast growth factor (FGF)21 is an endocrine hormone that is expressed in multiple tissues and functions physiologically to maintain energy homeostasis. FGF21 is being pursued as a therapeutic target for diabetes and obesity because of its rapid and potent effects on improving insulin sensitivity. However, whether FGF21 enhances insulin sensitivity under physiologic conditions remains unclear. Here, we show that liver-derived FGF21 enters the circulation during fasting but also remains present and function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

41
509
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 494 publications
(555 citation statements)
references
References 23 publications
41
509
5
Order By: Relevance
“…To investigate the effect of endogenous FGF21 in more detail, fasting-refeeding experiments were performed using WT and FGF21-deficient mice. Consistent with previous studies (2,19), detectable levels of plasma FGF21 were observed even during refeeding, although hepatic FGF21 mRNA levels were significantly decreased ( Fig. 6A and B).…”
Section: Fgf21 Reduces Postprandial Er Stresssupporting
confidence: 81%
See 1 more Smart Citation
“…To investigate the effect of endogenous FGF21 in more detail, fasting-refeeding experiments were performed using WT and FGF21-deficient mice. Consistent with previous studies (2,19), detectable levels of plasma FGF21 were observed even during refeeding, although hepatic FGF21 mRNA levels were significantly decreased ( Fig. 6A and B).…”
Section: Fgf21 Reduces Postprandial Er Stresssupporting
confidence: 81%
“…Plasma FGF21 and hepatic FGF21 mRNA levels are known to increase during fasting via PPARa (2,4). Although FGF21 gene expression is reduced by refeeding, a significant amount of circulating FGF21 was reported during the postprandial state (19). Based on these reports, we hypothesized that FGF21 may regulate postprandial ER stress.…”
Section: Fgf21 Reduces Postprandial Er Stressmentioning
confidence: 95%
“…FGF21 is induced by PPARα in the liver in response to fasting, PPARα agonists, and a highfat and low-carbohydrate ketogenic diet [8][9][10][11][12]. In addition, FGF21 is a downstream target of PPARγ and is required for the anti-diabetic effects of PPARγ agonists [13].…”
Section: Discussionmentioning
confidence: 99%
“…Although FGF21 is expressed in multiple organs, including the adipose tissue, thymus, skeletal muscle, and pancreas, it is primarily secreted by the liver as an endocrine hormone [9,10]. Circulating FGF21 is liverderived and is elevated in mice fed a high-fat diet [10].…”
Section: Real-time Quantitative Reverse Transcription-polymerase Chaimentioning
confidence: 99%
See 1 more Smart Citation